Les Sites archéologiques en Crimée et au Caucase durant l'Antiquité tardive et le haut Moyen-Age - Kazanski, Michel, (Colloquia Pontica ;, 2000)
The volume is devoted to the archaeological finds of late Roman and early Mediaeval periods in the northern Black Sea littoral and eastern Pontus. This collection of articles discusses the relationship between West and East, North and South in Roman and Mediaeval times. Most of the articles offer analysis of archaeological finds and sites in the Crimea studies in recent years. This book is richly illustrated.